2020
DOI: 10.1109/access.2020.3019334
|View full text |Cite
|
Sign up to set email alerts
|

A Study of South Asian Websites on Privacy Compliance

Abstract: Privacy laws in South Asian countries are still at a nascent stage. Therefore, South Asian websites are susceptible to user privacy violation. This paper presents an assessment of website privacy policies from 10 sectors in the three largest South Asian economies, namely, India, Pakistan, and Bangladesh. Using a manual qualitative analysis on a dataset of 284 popular websites, we assessed the policies based on accessibility, readability, and compliance with 11 privacy principles. Our findings show that overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Numerous studies have examined privacy statements on websites to analyze their content and compliance with relevant laws and regulations. Examples of such studies include investigations into privacy policies on municipal websites in the Netherlands [13] , Chinese city government websites [12] , Portuguese municipal websites [5] , and South Asian websites [14] . These studies have found that privacy statements' availability, findability, and conformity varied greatly.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have examined privacy statements on websites to analyze their content and compliance with relevant laws and regulations. Examples of such studies include investigations into privacy policies on municipal websites in the Netherlands [13] , Chinese city government websites [12] , Portuguese municipal websites [5] , and South Asian websites [14] . These studies have found that privacy statements' availability, findability, and conformity varied greatly.…”
Section: Methodsmentioning
confidence: 99%
“…Research on privacy policy assessment has been conducted in various regions worldwide, including China [12] , EU [13] , [5] , [10] , and South Asian [14] , from both government [13] , [5] , [12] and business [14] contexts. Previous studies primarily involved surveying websites to evaluate compliance of privacy policies with personal data protection laws in each country based on predetermined privacy principles [5] , [10] , [15] , [13] , [12] , [14] , [16] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berdasarkan pada permasalahan tersebut, maka dalam penelitian dirancang dan diimplementasikan sebuah aplikasi cerdas berbasis web yang ditujukan untuk membantu transaksi barang bekas/loak. Website [3]-[5] merupakan bagian dari Teknologi Informasi yang memanfaatkan Internet, yang diciptakan untuk mempermudah manusia dalam pekerjaannya seharihari, meningkatkan produktivitas dan hasil, dan juga mengefisienkan sumber daya manusia sehingga dapat diberdayakan untuk hal lain yang masih membutuhkan tenaga manusia [6]- [8]. Internet telah menjadi sumber yang paling banyak digunakan untuk mencari informasi yang dibutuhkan ia didukung oleh mesin pencari (search engineI) yang memudahkan pengguna mencari halaman-halaman web yang dibutuhkannya.…”
Section: Pendahuluanunclassified